(untitled) (Italian Journal of Public Health, 2011)
Background: The incidence of melanoma has steadily increased worldwide and shows geographical variability according to latitude. The aim of this study was to describe the incidence of cutaneous malignant melanoma (CMM) cases in the Province of Palermo during the period 2003-2005. Methods: 231 incident cases of CMM, registered by the Cancer Registry of Palermo, were analysed. Anatomic localization, histological type, thickness, ulceration, margins, any lymph node involvement and metastases were evaluated. A statistical analysis of survival rates was performed. Results: Distribution by sex and stage of diagnosis showed a slight, but not significant, difference between females and males diagnosed both in early and late stage CMM. Age incidence rates were higher in women before the age of 40 and in men over the age of 50. No statistically significant difference in stage was observed between residents in Palermo and of its Province. 148 cases (64%) were found in people living in Palermo, with an incidence rate (EU) of 7.2 over 100,000 in males and 6.1 in females, while in the province the incidence rate was lower (4.7 vs 3.9 ). Univariate analysis by gender showed better survival in females than in males and a better survival for age <49 and for stage I-II at diagnosis (p<0.05). Multivariate analysis including gender, age and cancer stage showed that survival is significantly positively related to earlier stage (p<0.05) and younger age (p=0.01) but not to sex (p=0.19). Conclusions: Diagnosis of CMM is mainly performed in the early stages, in both sexes and regardless of residence, suggesting no difference in early diagnosis and access to care between city and province. The incidence of CMM appears to be higher in the city compared to the province. Survival following diagnosis was strongly, and independently, related to age and stage of CMM, while gender did not significantly predict survival.